Lung Tuberculosis with suspect Peritonitis Tuberculosis: Case Report - Anak Agung Gde Upeksha; Hermantoputra Halim, Steven (Malang Respiratory Journal, 2023)
Background: Tuberculosis is an infectious disease that caused by Mycobacterium Tuberculosis Complex. Tuberculosis is one of the oldest disease and cause death worldwide. Gastrointestinal TB is uncommon Peritoneal TB commonly caused pain as its presenting manifestation with abdominal sweeling, fever, weight loss and anorexia. Active pulmonary TB is uncommon in patients with peritoneal TB Case Ilustration: A 19-year-old female came to Emergency Room with chief complaint of cough since 2 months ago accompanied with greenish phlegm. Patient also complaint shortness of breath, fever since 2 weeks ago, and also loss of appetite, weight loss around 8kg since 2 months ago. Patient also had nausea without constipation, patient had no history of previous illness and no one in the family was sick or currently on medication. On physical examination we found oxygen saturarion 93% room air, ronchi on left and right lung, and also distended abdomen, with ascites. Discussion: In This patient, Chest X-ray showed suspicion of miliary TB and minimal pleural effusion with Gene Xpert MTB/RIF showed positive. CT scan abdomen suggest wet type TB peritonitis. Patient with peritoneal TB concomitant with pulmonary TB are found less than 25% patients. In this patient, Gene Xpert MTB/RIF showed positive and CT scan abdomen suspicion peritoneal TB. Other examinations such as histopathological should be done to diagnose peritoneal TB. Conclusion: The symptoms of pulmonary TB and peritoneal TB are slightly different and also could be overlapping. Initial examination needs to be done so physician can give antituberculosis treatment and it can reduce risk of mortality.